Beautiful data a history of vision and reason since 1945 - Halpern, Orit 1972- (Experimental futures, 2014)
Prologue: Speculating on sense -- Introduction: Dreams for our perceptual present -- Dreams for the perceptual present : temporality, storage, and interactivity in cybernetics -- Communicative objectivity : design, knowledge, and the interface -- The measure of reason and the art of visualization : transforming rationality, method, and logic in the social and human sciences -- The governance of sense: designing information and reconfiguring population circa 1959